Exploring the Depths: Investigating the Degree of Foreign Language Classroom Anxiety among English for Specific Purposes (ESP) Learners - Agustina Hananingsih (Journal of Literature Language and Academic Studies, 2023)
This research aims to investigate the prevalence of Foreign Language Classroom Anxiety (FLCA) within the context of English for Specific Purposes (ESP) program. The study involved 13 participants enrolled in an ESP program at an English private course in Yogyakarta, with ages ranging from 16 to 33 years. Data was collected using a Google Form questionnaire comprising 33 items adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz, Howitz, and Cope (1986). The results revealed that a solitary participant maintained a relaxed disposition during class, while the majority of learners reported experiencing mild to elevated levels of FLCA. Communication apprehension emerged as the predominant contributor to FLCA, with fear of negative evaluation ranking as the second most influential factor. In contrast, test anxiety was identified as the least consequential factor impacting the participants’ levels of FLCA.